PENGARUH VARIABEL MAKROEKONOMI DAN HARGA SAHAM ASING TERHADAP INDEKS HARGA SAHAM GABUNGAN - R Safiroh Febrina; Sumiati Sumiati; Kusuma Ratnawati (University of Merdeka Malang, 2018)
Abstract : This study aimed to analyze the effect of macroeconomic variables and foreign stock price on Jakarta Composite Index (JCI) in Indonesia Stock Exchange covering the data period from January 2008 to December 2015. The methodology applied initially used the standard time series techniques, Vector Autoregression (VAR). The result showed that JCI are influenced with the selected macroeconomic and foreign stock price. Increasing in industrial production index and inflation will increase JCI, but exchange rate (Rp/USD) will decreases it. Money supply (M2) and interest rate is found insignificant on JCI. Strait Times Index, Philippines Stock Exchange Index and Dow Jones Industrial Average are found positively and significantly influenced JCI. However, Nikkei 225 and Shanghai Composite Index negatively and significantly influenced JCI. Kuala Lumpur Composite Index and stock Exchange of Thailand insignificant influenced JCI. Our finding suggest that JCI can be influence by macroeconomic variables and stock price in develop country and countries that are in the same region. DOI : https://doi.org/10.26905/jbm.v5i1.2321